The Effect of the Global Positioning System on the Driving Performance of People with Mild Alzheimer's Disease - Yi, Jewel; Lee, Hoe; Parsons, Richard; Falkmer, Torbjorn (S. Karger AG, 2014)
Introduction: The initial symptoms of Alzheimer's disease (AD) include attention deficits, memory loss and deficiencies in topographic and spatial orientation. People with AD may have way-finding difficulties in driving due to the deterioration of their navigation ability. Although the use of the Global Positioning System (GPS) has been proven to be a useful aid for older people in driving, there is no evidence to suggest that the benefit could extend to drivers with AD. Aim: This study aims to investigate the effectiveness of the GPS in assisting drivers with mild AD in finding their destination safely. Method: Twenty-eight drivers with mild to very mild AD, diagnosed by a general practitioner or a psychogeriatrician, completed all clinical and psychometric assessments including the Mini Mental State Examination, Trail Making Test B and Doors and People Test. During the driving assessment, 3 driving trials with different settings (normal, visual-only and audio-only) of the GPS were administered to all participants. The participants were required to follow instructions from the GPS and perform a variety of driving tasks on a driving simulator. The driving performances of participants were assessed by criteria specific to AD drivers. The driving assessment criteria were first combined to form the overall driving performance score: a higher score indicated a better overall driving performance. The other outcome of this study was the success of participants to navigate to a predetermined destination. Results: The driving performance of participants was different among the 3 settings (F = 72.8, p < 0.001) and the pairwise comparison between the 3 settings was significant (p < 0.001). The driving performance score was highest in the audio-only setting (mean: 20.0, SD: 2.2), moderate in the normal setting (mean: 16.7, SD: 2.6) and lowest in the visual-only setting (mean: 14.3, SD: 3.3). When compared with the visual-only setting, drivers using the audio-only setting (OR: 37.2, 95% CI: 9.2-151.2) and normal setting (OR: 37.2, 95% CI: 4.8-286.9) were more likely to successfully find their destination (p < 0.05). Conclusion: This study has found that using single, simple auditory instructions with the absence of the visual output of the GPS could potentially help people with mild AD to improve their driving ability and reach their destination.